STUDENTS’ PROBLEMS IN SPEAKING OF THE SECOND YEAR STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM AT MADAKO UNIVERSITY - Hidayati, Hidayati (Universitas Madako Tolitoli, 2021)
This research aimed to find out the students’ problems in speaking at second semester of English Department at Madako University. The data was collected from 16 students at Second Semester of English Department at Madako University by using purposive sampling technique. This research design used qualitative design mixed with quantitative approach. The instrument used to collect the data was questionnaire and documentation. From the result, the researcher found some conclusion of students’ problems in speaking. The first problem of the students in psychological, most students revealed that they have problem with their self confidence. The students feel shyness while speaking English. They also feel anxious when they would speak English. And next most of students fear of mistakes when speaking. There were some students feel lack of motivation. The second problem of the students in the language, there were three problems that make most students inactive in speaking English. Most students had problems in grammar; they did not understand the grammar rules. And then some students have problems in pronunciation; they did not know the correct pronunciation of words. And lack vocabulary became their third problem in speaking; they lacked vocabulary, so they always translated from Indonesia to English.